2020
DOI: 10.1242/jeb.216754
|View full text |Cite
|
Sign up to set email alerts
|

Neev, a novel long non-coding RNA, is expressed in chaetoblasts during regeneration of Eisenia fetida

Abstract: Eisenia fetida, the common vermicomposting earthworm, shows robust regeneration of posterior segments removed by amputation. During the period of regeneration, the newly formed tissue initially contains only undifferentiated cells but subsequently differentiates into a variety of cell types including muscle, nerve and vasculature. Transcriptomics analysis, reported previously, provided a number of candidate non-coding RNAs that were induced during regeneration. We found that one such long non-coding RNA (lncRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The differences in the stages of regeneration used in different works also decrease the value of the published results for comparative transcriptomics (see Table 1). [24], Pristina leidyi [25], Eisenia fetida [26,27], Sphaerosyllis hystrix and Syllis gracilis [22], Eisenia andrei [28], Eudrilus eugeniae [29], and Lumbriculus variegatus [30] have lent support to the idea that a large and diverse repertoire of genes are up-regulated or down-regulated during regeneration in annelids. Many studies have shown the activation of, not only housekeeping genes and components of signaling pathways (FGF, MAPK, BMP, WNT, Hedgehog, Notch), but also genes that have specific functions in development, including homeobox genes (Hox, homothorax, even-skipped, msx), brachyury, factors related to nervous system development (gs, elav, slit), and stem-cellness [22,26,29,30].…”
Section: The Transcriptomic Eramentioning
confidence: 93%
See 2 more Smart Citations
“…The differences in the stages of regeneration used in different works also decrease the value of the published results for comparative transcriptomics (see Table 1). [24], Pristina leidyi [25], Eisenia fetida [26,27], Sphaerosyllis hystrix and Syllis gracilis [22], Eisenia andrei [28], Eudrilus eugeniae [29], and Lumbriculus variegatus [30] have lent support to the idea that a large and diverse repertoire of genes are up-regulated or down-regulated during regeneration in annelids. Many studies have shown the activation of, not only housekeeping genes and components of signaling pathways (FGF, MAPK, BMP, WNT, Hedgehog, Notch), but also genes that have specific functions in development, including homeobox genes (Hox, homothorax, even-skipped, msx), brachyury, factors related to nervous system development (gs, elav, slit), and stem-cellness [22,26,29,30].…”
Section: The Transcriptomic Eramentioning
confidence: 93%
“…The diameter of giant axons and the abundance of gap junctions, as well as the The molecular basis of neural regeneration has been poorly investigated. Works on the unbiased analysis have identified both conservative and novel potential drivers of reparative neurogenesis [22,23,[26][27][28]98,99]. Among the NS-associated genes, the strongest differential expression was noted for such neurodifferentiation markers as glutamine synthetase, slit, elav, neurofilament NF70, and Nerve Growth Factor [22,23,26,28,39,100].…”
Section: Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…lncRNAs can act as a decoy for miRNA that binds to specific mRNA targets, leading to increased expression of the mRNA targets (Ebert and Sharp, 2010). In the annelid Eisenia fetida , neev , a lncRNA has been related to the process of chaetogenesis acting as miRNA decoy (Patel et al, 2020). We identified numerous miRNAs that might interact with both id13944 and id3252 lncRNAs in P. dumerilii (Supplementary Materials 9 and 10), hinting at a role as a miRNA decoy.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic regulation of regeneration is achieved by three main mechanisms: DNA methylation, histone modification and noncoding RNAs ( Rouhana and Tasaki, 2015 ). There are already reports of the relevance of epigenetic regulation for development and regeneration of annelids ( Giani et al, 2011 ; Niwa et al, 2013 ; Kozin and Kostyuchenko, 2015 ; Bhambri et al, 2018 ; Bicho et al, 2020 ; Singh Patel et al, 2020 ; Planques et al, 2021 ). An analysis of the regeneration transcriptome of Lumbriculus variegatus ( Tellez-Garcia et al, 2021 ) in search for transcripts encoding for writers and erasers of DNA methylation revealed genes encoding for DNA methyltransferases and several ten-eleven translocation proteins, as well as histone acetyltransferases, histone deacetylase, histone methyltransferases, and histone demethylases.…”
Section: The Future: Lumbriculus Enters the Genomics Eramentioning
confidence: 99%